Investigation of physical activity level in COVID-19 pandemic period of amateur and professional soccer players - Burak Cagdanlioglu, M.; Biçer, M.; Vural, M. (European Journal of Physical Education and Sport Science, 2021)
The aim of this study is to examine the physical activity levels of amateur and professional football players during the covid-19 pandemic period. For this purpose, 54 amateur female, 69 amateur male and 36 professional male football players participated in the study. The long version of the international physical activity questionnaire (IPAQ) was used to determine the physical activity levels of the participants. SPSS 22.0 (SPSS Inc., Chicago, Illinois, USA) program was used for statistical processing of the data. Values were presented as minimum, maximum, mean, standard deviation, and standard error. Significance level was accepted as p<0.05. Kolmogorov-Smirnov test was used for normality test. One Way Anova and LSD tests were performed to analyze the differences between groups. As a result of the statistical analysis, a significant difference was found in the total MET scores of amateur women and amateur men for home-garden work (p<0.05). A significant difference was found in the transportation section bicycle MET scores of the professional male and amateur female groups (p<0.05). There was no significant difference between the MET scores of the age and sports age groups of the participants (p>0.05). As a result, it can be said that the physical activity levels of amateur women, amateur men and professional men groups are low.